Pengaruh Penggunaan Step Up Voltage Dan Variasi Bahan Bakar Terhadap Konsumsi Bahan Bakar Pada Motor Honda Beat - Ali Akbar Fillayati; Danar Susilo Wijayanto; Ngatou Rohman (Nozel : Jurnal Pendididikan Teknik Mesin, 2022)
The purpose of this study: (1) To investigate the effect of step up voltage on fuel consumption on Honda Beat motorcycles. (2) Investigating the effect of variations in the use of pertalite and pertamax fuels on the use of step up voltage on fuel consumption on Honda Beat motorcycles. (3) Investigating the best configuration on the use of Step Up Voltage on fuel consumption on a Honda Beat motorcycle. The research method used is descriptive investigation. The data obtained from the experimental results are entered into a table displayed in the form of a graph for later analysis. The descriptive research that will be used is a comparative study. The independent variables in this study: (1) The use of step up voltage (2) Variations in the use of pertalite and pertamax fuels (3) Variations in engine speed of 1500 rpm, 2000 rpm, and 2500 rpm. (4) Voltage variations are 13.7 V, 13.9 V, 14.1 V, 14.3 V, 14.5 V, and 14.7 V. The dependent variable in this study is fuel consumption under standard conditions and those who have used step-up voltage. The control variable used was a 2013 Honda Beat motorcycle and a 50 ml measuring cup. The results of this study: (1) The use of step up voltage affects the fuel consumption of Honda Beat motorcycles in 2013 because there is a difference in fuel consumption before using step up voltage and after using step up voltage. The use of this tool has been proven to be able to reduce fuel consumption by 0.87 ml/minute at 1500 rpm, with these results, the use of step up voltage affects the combustion quality of the fuel and air mixture in the combustion chamber of a motor vehicle which becomes more perfect due to a decrease the fuel consumption of the tested motor vehicle. (2) The use of Pertamax fuel can reduce fuel consumption. The average fuel consumption produced is 6.59 ml/minute, a decrease of 2.33 ml/minute from pertalite fuel. (3) The best configuration to obtain the lowest fuel consumption is to use a step up voltage with Pertamax fuel at a voltage of 14.3 V. This configuration is the best than the other configurations, with a fuel consumption of 3.76 ml/minute at 1500 rpm.